Pengaruh Kualitas Pelayanan, Kepuasan Dan Loyalitas Pelanggan Terhadap Pendapatan (Studi Kasus Pada Jasa Pengiriman JNE Umar Ar-Rasyid Brebes) - Anisa Fitri; Dewi Indah Mulyani; Nur Afrida (Journal Economic Excellence Ibnu Sina, 2023)
This study aims to determine the effect of service quality, customer satisfaction and loyalty on income at the JNE Umar Ar-Rasyid Brebes delivery service. The variables of this research are service quality, satisfactiion, costomer loyalty and income. The sample of this research is 100 respondents. This type of research is quantitative. The result of the F test concluded that service quality, costomer satisfaction and loyalty simultaneously have a significant effect on income because the value of Fcount>Ftable or 57.789>2.70 has a significance value of 0.000<0.05. The result of the T (Partial) test for service quality have a significant effect on income because the value of tcount>ttable or 3.808>1.984 with a significance value of 0.000<0.05. Satisfaction has no significant effect on income because the value of tcount>ttable or 1.874<1.984 ang a significance value of 0.064>0.05. Costomer loyalty has a significant effect on income because the value of tcount>ttable or 3.357>1.984 and a significance value of 0.001<0.05.